Extent and direction of introgressive hybridization of mule and white‐tailed deer in western Canada. (1st June 2021) - Russell, Ty; Cullingham, Catherine; Ball, Mark; Pybus, Margo; Coltman, David
Abstract: Hybridization of mule deer ( Odocoileus hemionus ) and white‐tailed deer ( O . virginianus ) appears to be a semi‐regular occurrence in western North America. Previous studies confirmed the presence of hybrids in a variety of sympatric habitats, but their developing molecular resources limited identification to the earliest, most admixed generations. For this reason, estimates of hybrid production in wild populations often rely on anecdotal reports. As well, white‐tailed deer populations' continued encroachment into historically mule deer‐occupied habitats due to changes in land use, habitat homogenization, and a warming climate may increase opportunities for interspecific encounters. We sought to quantify the prevalence and extent of hybrid deer in the prairies of western Canada using a SNP assay with enhanced discriminating power. By updating the available molecular resources, we sought to identify and characterize previously cryptic introgression. We also investigated the influence of various parameters on hybridity by way of logistic regression. We observed overall hybridization rates of 1.0%, slightly lower than that reported by previous studies, and found white‐tailed‐like hybrids to be more common than their mule deer‐like counterparts. Here, we build upon past studies of hybridization in North American deer by increasing hybrid detection power, expanding sample sizes, demonstrating a new molecular resource applicable to future research and observing asymmetrical directionality of introgression.